2017
DOI: 10.22214/ijraset.2017.10093
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Human Behavior through Handwriting

Abstract: Handwriting Analysis is described as a scientific study. It is analysis of human handwriting. The scientific name for handwriting analysis is Graphology. It is a way of interpreting behaviour from peculiarities in handwriting. All that is part of the mind is reflected by an individual in many ways, writing being one. Professional handwriting examiners called graphologists predict the personality of the writer with a piece of handwriting. Accuracy of handwriting analysis depends on the skills of the graphologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…CNN and SVM classifiers were used. Chanchlani et al [8] created five labels for their dataset namely Persistent, Excitable, Criminal Intent, Narcissistic, Honest and self-centred. TensorFlow and OpenCV were used.…”
Section: Related Workmentioning
confidence: 99%
“…CNN and SVM classifiers were used. Chanchlani et al [8] created five labels for their dataset namely Persistent, Excitable, Criminal Intent, Narcissistic, Honest and self-centred. TensorFlow and OpenCV were used.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, graphology-based behavioural analysis has acquired prominence due to its broad range of applications in fields such as psychology, education, medicine, criminal detection, marriage guidance, commerce, and recruitment, etc. Several methods for predicting person behaviour based on graphology-based handwriting have been proposed in the literature; however, these methods require human intervention to identify behaviour [13,14]. It is observed that graphology-based human behaviour analysis lacks a mathematical foundation.…”
Section: Introductionmentioning
confidence: 99%